Design of temoporfin molecules functionalized with two-photon absorbing antennas and their potential use in photodynamic therapy - Uyar, Ege Su. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2023., 2023)
Since its approval in 2003 by the European Agency of Medicine (EAM), temoporfin has been clinically used as a photosensitizer for photodynamic therapy. However, Temoporfin’s significant limitations such as low solubility in water and high aggregation probability in biological environments have created a window of opportunity for increasing its efficacy through modifications. In this thesis, three new drug molecules are proposed and obtained by modifying the temoporfin molecule with the addition of three different two-photon absorbing (TPA) dye molecules. To explore the newly proposed molecules’ suitability to photodynamic therapy, various theoretical chemistry tools are utilized such as Density Functional Theory (DFT), and Time- Dependent Density Functional (TD-DFT) on various levels of theory for quantum mechanical (QM) calculations. The results shed light on the electronic spectra of candidate drug molecules. Later, molecular dynamic techniques are exploited for further analysis of the novel drug molecules’ behavior in settings similar to biological environments.
Keywords: Photochemotherapy.; Cancer -- Photochemotherapy.; Temoporfin.